Common Fixed Point Theorems for Nonlinear Contractive Mappings in Dislocated Metric Spaces. (12th March 2013) - Ren, Yijie; Li, Junlei; Yu, Yanrong
Abstract : In 1986, Matthews generalized Banach contraction mapping theorem in dislocated metric space that is a wider space than metric space. In this paper, we established common fixed point theorems for a class of contractive mappings. Our results extend the corresponding ones of other authors in dislocated metric spaces.